Seafood and freshwater toxins [ pharmacology, physiology and detection - Botana, Luis M. (CRC Press, 2014)
"This book provides an overview of the current state of knowledge from several perspectives. Incorporating toxicology, chemistry, ecology, and economics, the book covers the biological aspects of the bloom and the effects and actions of each toxin, with emphasis on human response. It discusses the use of animals, receptors, antibodies, and aptamers as tools for method development. It highlights the legal and economic perspectives of toxic incidence in industrial activity and international regulation and monitoring programs"